Substance P: an immunohistochemical and biochemical study in human gingival tissues. A role for neurogenic inflammation? - Bartold, P M; Kylstra, A; Lawson, R (Journal of periodontology (1970), 1994)
Substance P has been studied in relation to its distribution within gingival tissues as well as its effect on cultured human gingival fibroblasts. The tissue distribution was varied depending on the degree of inflammation present. In healthy tissues substance P was found in the connective tissues interspersed between the collagenous elements and was particularly prominent in the areas immediately subjacent to the epithelial rete pegs. In inflamed tissues, substance P was markedly increased particularly around the blood vessels as well as in close association with much of the inflammatory cell infiltrate. The effect of substance P on human gingival fibroblast proliferation was monitored by [3H]-thymidine incorporation and indicated substance P to be mitogenic for these cells at low concentrations (1 x 10(-9) M) and tended towards an inhibitory effect at higher concentrations (1 x 10(-4) M). Substance P did not have any effect on the release of either total proteins or proteoglycans into the culture medium. However, exposure of the cells to substance P did cause a greater accumulation of both total protein and proteoglycan with the cell layer material. These findings suggest a potential role for substance P on gingival tissues and in particular their resident fibroblastic cells and can therefore be used as a basis for more detailed studies into the relationship between neuropeptide release associated with neurogenic inflammation and periodontal pathology.